Developing inclusive practices in higher education - Magbanua, Dennis M., FSC (Animo Repository, 2018)
There is an increasing number of diversely-gifted learners and learners with disabilities entering higher education in Asia. Colleges and universities face a variety of challenges on how to adapt and address the needs of these unique learners. In this reflective documentation, the case of De La Salle-College of Saint Benilde, a Philippine higher education institution recognized for its active pursuit of inclusive education, is provided as a benchmark for institutions planning to develop inclusive education programs. Using the Index for Inclusion framework of Booth and Ainscow (2016), this documentation highlights the three key dimensions of (l) creating inclusive culture, (2) developing inclusive policies, and (3) evolving inclusive practices in building an inclusive educational institution. Keywords: Inclusive education) inclusive higher education) educational leadership) educational management) organizational change